Attempts at Polandʼs cooperation with the Kemalist Turkey in the Balkan Entente period - Chmielowska, Danuta (Balcanica Posnaniensia. Acta et studia, 2010)
The article analyzes the attempts at political and economic rapprochement between the Second Polish Republic and Kemalist Turkey during the period of the Balkan Entente (1930s). The starting point of the research is Józef Piłsudski’s political concept, which aimed to build a regional security system in Central and Eastern Europe based on cooperation with the Balkan states and Turkey. The author presents the historical background – from the establishment of the Republic of Turkey and its modernization to the transformation of Ankara’s foreign policy – and examines the obstacles that hindered the strengthening of Polish-Turkish relations, particularly the divergent relations of both countries with the Soviet Union. The study draws upon archival materials (including documents from the Polish Ministry of Foreign Affairs preserved in the Central Archives of Modern Records) as well as academic literature on the history of diplomacy and international relations. The author applies the methods of source analysis and comparative analysis of the foreign policies of Poland and Turkey in the context of contemporary alliance systems. The findings indicate that, despite mutual interest and the signing of several trade and settlement agreements, Polish-Turkish cooperation did not reach a strategic dimension. Polish diplomacy viewed Turkey as a potential ally in building a pro-French bloc of Central European states, but the Turkish policy – oriented toward maintaining balanced relations with the USSR and Germany – limited the possibility of closer rapprochement. The article concludes that, although these initiatives did not lead to lasting political results, the efforts undertaken during the Balkan Entente period contributed to strengthening Poland’s regional position and to consolidating a favorable image of Polish-Turkish cooperation.